Renal vascular variations among kidney donors presented at the national kidney transplantation center, Addis Ababa, Ethiopia - Abinet Gebremickael; Mekbeb Afework; Habtamu Wondmagegn; Mahteme Bekele (Elsevier, 2021)
Background: Renal vascular anatomy is known for presenting a wide range of variations as illustrated by previous cadaveric and imaging studies. However, the pattern of renal vascular variations is not well known in Ethiopian population. Hence, the present study is aimed at evaluating the renal vascular variations among kidney donors presented at the national kidney transplantation center, Addis Ababa, Ethiopia. Methods: Institution based cross-sectional study was performed through a retrospective review of the charts of kidney donors underwent donor nephrectomy at the transplantation center from 2015 to 2020. We studied 120 donors, 61 (50.8 %) males and 59 (49.2 %) females. Age range is 20-62 years (mean = 34.88 ± 11.4). Descriptive statistical analysis was done by using SPSS version 25. Result: There were 240 kidneys from 120 donors. Renal vascular variations of any kind were found in 59 kidneys (25 right and 34 left) among 46 (38.8 %) donors (29 male, 17 female). Variations were significantly more common in males, P = 0.035. Arterial variations identified in this study were accessory renal artery, which is the most common variation (23.3 %), early branching (prehilar) renal artery (10.8 %) and unusual branching pattern of renal artery (4.1 %). The identified renal venous variations were accessory renal vein (9.1 %), late confluence of renal vein (0.8 %) and retroaortic left renal vein (0.8 %). Vascular variants showed no statistically significant association with laterality. Conclusion: This study has shown that variations of the renal arterial and venous anatomy are a frequent finding among Ethiopians. All of the described variants have significant implications for treatment planning for a variety of surgical procedures. Radiologists and surgeons must be aware of all possible variants to avoid diagnostic pitfalls and for optimization of surgical techniques to prevent avoidable postsurgical morbidities.